A semantic-based representation and analysis of monitoring data for self-adaptive systems. (2017) - Jemal, Ahmed; Halima, Riadh Ben; Ktait, Henda; Jmaiel, Mohamed
In the current decade, computing turns towards smart, mobile and ambient devices. Consequently, applications and services have to be aware in order to react to a highly dynamic context (available resources, environmental conditions etc.) and adapt their structures and behaviours. In a such environment (e.g., smart buildings), interoperability is highly recommended, especially for contexts where connected entities need to understand one another and an analysis module is built based on exchanged data querying in order to detect alerting situations. In this paper, we propose an ontology model for smart building allowing the representation of smart entities monitoring data and a rule based analysis. We elaborate domain ontology for the smart building space and implement a prototype using Protégé and Pellet. Furthermore, we define smart rules using SWRL in order to analyse the context and generate alerts regarding abnormal behaviours.